2021
DOI: 10.17644/sbd.898381
|View full text |Cite
|
Sign up to set email alerts
|

Engelli Sporcuların Objektifinden Spor Deneyimini Görmek: Engelleyici Faktörlerin Sosyo-Ekolojik Model Perspektifinden Analizi

Abstract: The aim of this study was to understand the experiences of athletes with a physical impairment regarding the constraints they face in their participation in sports and how these constraints affect their participation in sports from the Socio-Ecological Model (SEM) perspective with the photo voice method. In this qualitative study based on the interpretative paradigm, the participants were selected according to the criterion sampling method, which is one of the purposeful sampling methods. Four wheelchair track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…In light of these theoretical frameworks, the study's findings suggest that societal evaluations of participants can be illustrative of ableism. Moreover, negative attitudes encountered from others (Argan et al, 2021;Koçak et al, 2023) and a lack of social awareness (Arnell et al, 2020;Ballas et al, 2022) are identified as influential factors in the sports participation of individuals with disabilities.…”
Section: Obstacles To Sports Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of these theoretical frameworks, the study's findings suggest that societal evaluations of participants can be illustrative of ableism. Moreover, negative attitudes encountered from others (Argan et al, 2021;Koçak et al, 2023) and a lack of social awareness (Arnell et al, 2020;Ballas et al, 2022) are identified as influential factors in the sports participation of individuals with disabilities.…”
Section: Obstacles To Sports Participationmentioning
confidence: 99%
“…It is observed that besides the barriers encountered by physically disabled individuals in many areas of life, they also encounter various inhibiting factors in the field of sports . A review of the literature reveals several such impediments, including transportation challenges (Esatbeyoğlu and Karahan, 2014;Durmuş and Sarol, 2023;Kumcağız and Çayır, 2018;Küçük, 2024;Uzun et al, 2023), negative attitudes (Argan et al, 2021;Koçak et al, 2023), economic constraints (Murphy et al, 2008), health issues stemming from physical disabilities (Jaarsma et al, 2014a;Jaarsma et al, 2014b;Sarol, 2024), lack of energy (Jaarsma et al, 2015), and time constraints (McLoughlin et al, 2017). Moreover, inadequate training of trainers (Shields and Synnot, 2014;Ünlü et al, 2024), inappropriate facilities and equipment for disabled individuals (Caracci, 2019;Columna et al, 2017;Sarol, 2024;Shields and Synnot, 2016;Çeviker, 2017), and societal unawareness (Arnell et al, 2020;Ballas et al, 2022) have been identified as additional inhibiting factors affecting sports participation.…”
Section: Introductionmentioning
confidence: 99%
“…ihtiyaçları ve bu ihtiyaçları karşılamak için yerine getirilmesi gereken ekonomik şartların sağlandıktan sonra kalan zamanlarda gerçekleştirdiği aktiviteler ise, serbest zaman aktiviteleri olarak açıklanmaktadır (Gürbüz & Henderson, 2014). Gerçekleştirilen veya tercih edilen serbest zaman aktiviteleri ve serbest zamana verilen anlam, bireylerin demografik özellikleri, ekonomik şartları, sahip olduğu aile yaşamı, alınan eğitim ve içinde yaşadığı toplumun özelliklerine farklılık göstermektedir (Argan, Gürbüz, Koçak & Atıcı, 2021;Gürbüz & Henderson, 2013). Serbest zaman aktivitelerine katılım sıklıkla yaşam kalitesi, motivasyon, sıkılma algısı ve doyum konuları ile ilişkilendirilmektedir (Choi & Yoo, 2017;Hartman ve diğ., 2020).…”
Section: Introductionunclassified
“…8 In Türkiye, studies also showed that among other barriers, environmental barriers including accessibility issues also prevent individuals with disabilities to participate in physical activity and/or sports. [9][10][11] Esatbeyoğlu and Güven-Karahan for example reported in their study that along with personal barriers individuals with disabilities cannot participate to sports because of accessibility issues regarding sports facilities. 9 Moreover, Argan et al reported that the presence of environmental barriers directly affect participation in sports especially for individu-als with physical disabilities.…”
mentioning
confidence: 99%
“…9 Moreover, Argan et al reported that the presence of environmental barriers directly affect participation in sports especially for individu-als with physical disabilities. 10 Paralympic athletes also reported environmental barriers including lack of accessible sports facilities and sports equipment to participate in sports and continue their training before big events such as Paralympics. 11 In order to overcome those barriers and welcome all participants to sport events and facilities, countries started to invest in initiatives designed to promote active lifestyle for all its citizens including individuals with disabilities.…”
mentioning
confidence: 99%